PENGARUH INDEPENDENSI, KOMPETENSI, PENGALAMAN DAN PENGETAHUAN TERHADAP TANGGUNG JAWAB AUDITOR DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Nindya Agustina, 08.05.52.0001; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2013)
Auditors are responsible for providing assurance and assessment of the financial statements presented by management of the company if it has been presented fairly and can be trusted or not. Intentional misstatement in fraud management (Fraudulent Financial Reporting) is the responsibility of public accountants to detect and find it, as this may affect the financial statements taken as a whole, both directly and indirectly. The purpose of this study was to find empirical evidence and analyze the influence of independence, competence, experience and knowledge of the auditors responsibility to detect fraud and error in the financial statements. The results of this study hoped to benefit particular companies and inputs for Public Accounting Firm. To test thehypothesisusedmultiple linear regression. The results of the regression analysis showed that the independence, experience and knowledge have a positive effect not significant for the auditors responsibility to detect fraud and error in the financial statements, while the competencies have a significant positive effect for the auditors responsibility to detect fraud and error financial statements.Keywords: Responsibility, Independence, Competence, Experience and Knowledge